The comparision of Iranian Physician and Nurses attitudes towards Do- Not- Resusciate Orders - Falahi, Masod; Bana Derakhshan, Homayoon; Borhani, Fariba; Pourhoseingholi, Mohamad Amin (Advances in Nursing & Midwifery, 2016)
Abstract: Background and Aim Decision making process about Do- Not-Resusciate (DNR) order is unique, since, it is the only treatment decision that should be taken in advance. Most physicians and nurses are not sure whether and when to make a decision about DNR order and its moral aspects. The current study is performed to compare and investigate nurses and physicians attitude about DNR order for patients in their final phases of life. Materials and Methods In this descriptive–comparative study, 152 physicians and 152 nurses have been studied. The sampling method was stratified sampling. The data gathering tools were a demographical questionnaire and a attitude questionnaire about DNR order. Results The nurses and physicians in this research with averages of 3.25 for nurses and 3.22 for physicians, had a positive attitude about DNR order. But there was no significant difference between the attitude average score of the physicians and nurses about DNR order (p>0.5). Nurses and physicians with experience of participating in implementation of cardiopulmonary resuscitation and DNR order, had more positive attitude toward DNR order Conclusions The findings suggest that there is no difference between the physician’s and nurse’s view about DNR order. Although there is a significant relationship between former experience of participating in implementation of cardiopulmonary resuscitation and DNR order with positive attitude about DNR order. Keywords Cardiopulmonary resuscitation; Physician; Nurse, Attitude